Availability and Adequacy of Instructional Facilities for the Implementation of Primary School English-Studies Curriculum in Edo South- Senatorial District - ADEYEMO, Fatima Moromoke (Ilorin Journal of Education, 2024)
This study assessed the availability and adequacy of physical and instructional facilities for the implementation of primary schools English Studies curriculum in Edo South Senatorial District. The study aimed to find out the state of building facilities in primary schools and if the schools were provided with standard libraries, language laboratories and instructional materials as recommended in the minimum education standard. Five (5) research questions were raised to guide the study. Descriptive survey research design was adopted for the study. The population comprised 6,513 primary schools teachers and 518 schools in Edo South Senatorial District. A total of 29 schools, 29 Head teachers and 348 teachers were selected using multistage random sampling technique. The research instruments were questionnaire and checklist which were validated by three psychometricians. Cronbach Alpha method was used to establish the reliability of the questionnaire with a reliability coefficient of 0.79. The data obtained were analysed using the percentages. The findings revealed gross inadequacy of physical and instructional facilities for the implementation of English Studies curriculum It was recommended that government and other stakeholders should improve on the provision of physical and instructional facilities required for the implementation of English Studies curriculum in line with the minimum education standard.